2020
DOI: 10.1111/ajco.13452
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of long non‐coding RNA function in colorectal cancer tumorigenesis

Abstract: Colorectal cancer (CRC) is one of the most common cancers globally. Although a variety of CRC screening methods have been developed, many patients are diagnosed at advanced stages of CRC with tumor invasion and distance metastasis. Several studies have suggested the long noncoding RNAs (lncRNAs) as one of the main contributors in CRC tumorigenesis, although the exact underlying mechanism of lncRNAs in CRC is still unknown. Numerous studies have indicated aberrant expression of lncRNAs in CRC through different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 196 publications
0
25
0
Order By: Relevance
“…In the last decade, considerable studies have identified that lncRNAs played critical roles in carcinogenesis and metastasis (Lv et al 2021 ; Yao et al 2019 ; Poursheikhani et al 2021 ). To data, the ceRNA hypothesis sparked new areas of lncRNA research on gene expression regulation, but some controversy still surrounded it (Tay et al 2011 ; Smillie et al 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, considerable studies have identified that lncRNAs played critical roles in carcinogenesis and metastasis (Lv et al 2021 ; Yao et al 2019 ; Poursheikhani et al 2021 ). To data, the ceRNA hypothesis sparked new areas of lncRNA research on gene expression regulation, but some controversy still surrounded it (Tay et al 2011 ; Smillie et al 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs can regulate gene expression, mainly at the post-transcriptional level, via various modes of direct action or as miRNA sponges or endogenous competitors, thus reducing their regulatory effect on target mRNAs [66]. The aberrant expression of lncRNAs, exemplified by lncRNA H19 and lncRNA 91H, an antisense gene of H19, has been implicated in the tumorigenesis and metastasis of different types of cancer, including CRC, where it is associated with a poor prognosis and a high risk of tumor metastasis [67,68]. Both LINC01354 and lncRNA CASC11 are upregulated in CRC and contribute to the pro-liferation, invasion, and metastasis of CRC via activation of the Wnt/β-catenin signaling pathway [69,70].…”
Section: Discussionmentioning
confidence: 99%
“…Several genetic variants located in lncRNA genes influence the risk of CRC development; polymorphisms in lncRNA HOTTIP, rs145204276 and rs55829688 in lncRNA GAS5, rs2839698 in lncRNA H19, rs2632159 in lncRNA PCAT1, rs2147578 in lnc-LAMC2-1:1, and rs664589 in MALAT1 were associated with a significantly increased CRC risk [67], while rs13252298 and rs1456315 in lncRNA PRNCR1 and rs1194338 in MALAT1 had protective effects on CRC [67,74]. It has been suggested that the rs664589 G allele alters the binding of MALAT1 to miR-194-5p, resulting in an increased expression of MALAT1 and enhanced CRC development and metastasis [75], while the rs2147578 in lnc-LAMC2-1:1 affects the sponging of miR-128-3p, which correlates with higher expression of the LAMC2 oncogene in CRC [76].…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs are a group of non-coding RNAs with more than 200 nt in length and with no or little capability of coding proteins [ 14 – 16 ]. They have been demonstrated to play different canonical roles in diverse biological processes such as cell proliferation, differentiation, and cellular development, carcinogenesis, and metastasis through regulating cornerstone genes expression [ 4 , 17 ]. Numerous investigations highlighted the crucial role of lncRNAs in cancer development and progression [ 18 ].…”
Section: Introductionmentioning
confidence: 99%